Kompetensi Guru Dalam Pembelajaran Di Sekolah Dasar Negeri 3 Wirosari Grobogan - Purwanto, Purwanto, Prof. Dr. Abdul Ngalim, M.M, M.Hum, Dr. Sumardi, M.Si (2016)
COMPETENCE LEARNING IN SCHOOL TEACHERS IN BASIC STATE 3 Wirosari GROBOGAN Author: Purwanto, Supervisor one: Abdul Ngalim, Counsellor two: Sumardi. Education Administration Studies Program, Graduate School, University of March, Surakarta. Email: wantopur770@gmail.com Abstract Teacher competence determines the success of the achievement of educational goals. The purpose of this study, there are three. 1) Describe the competence of teachers prepare lesson plans at State Elementary School 3 Wirosari Grobogan. 2) Describe the competence of teachers teaching practices at the State Elementary School 3 Wirosari Grobogan. 3) Describe the competence of teachers implement instructional evaluation at the State Elementary School 3 Wirosari Grobogan. Qualitative research conducted at the State Elementary School 3 Wirosari Grobogan. Sources of data on interviews with school principals, teachers, students, observation and documentation. Data collection techniques of interview, observation, document analysis. Data analysis used data reduction, data presentation and conclusion. The validity of the data triangulation data. The results of this study public elementary school teachers 3 Wirosari Grobogan own competence in learning good. 1) Competence of making the learning plan includes promissory notes, syllabi and lesson plans. Making learning Planning already contained the principles and components of good teaching preparation. There is a link between standard and basic competencies with competence achievement indicator. 2) Competence implementing teacher learning is good, include the implementation of learning with the indicator component can open a lesson, presenting the material, method, media / props, motivate students, organizing events, concludes the learning, provide feedback, and evaluate it. 3) Competence of teachers implement instructional evaluation. The evaluation was appropriate learning lesson preparation with steps evaluation. a) Planning evaluation. b) Implementation of evaluation. c) Processing evaluation data. d) Reporting the results of the evaluation of the evaluation. Learning outcomes achieved in State Elementary School 3 Wirosari Grobogan increase according to our expectations.